Dysregulation of Gap Junction Function and Cytokine Production in Response to Non-Genotoxic Polycyclic Aromatic Hydrocarbons in an In Vitro Lung Cell Model - Romo, Deedee (Cancers (Basel), 2019)
Polycyclic aromatic hydrocarbons (PAHs), prevalent contaminants in our environment, in many occupations, and in first and second-hand smoke, pose significant adverse health effects. Most research focused on the genotoxic high molecular weight PAHs (e.g., benzo[a]pyrene), however, the nongenotoxic low molecular weight (LMW) PAHs are emerging as potential co-carcinogens and tumor promoters known to dysregulate gap junctional intercellular communication (GJIC), activate mitogen activated protein kinase pathways, and induce the release of inflammatory mediators. We hypothesize that inflammatory mediators resulting from LMW PAH exposure in mouse lung epithelial cell lines are involved in the dysregulation of GJIC. We used mouse lung epithelial cell lines and an alveolar macrophage cell line in the presence of a binary PAH mixture (1:1 ratio of fluoranthene and 1-methylanthracene; PAH mixture). Parthenolide, a pan-inflammation inhibitor, reversed the PAH-induced inhibition of GJIC, the decreased CX43 expression, and the induction of KC and TNF. To further determine the direct role of a cytokine in regulating GJIC, recombinant TNF (rTNF) was used to inhibit GJIC and this response was further enhanced in the presence of the PAH mixture. Collectively, these findings support a role for inflammation in regulating GJIC and the potential to target these early stage cancer pathways for therapeutics.